Affective Antecedents of the Perceived Effectiveness of Antidrug Advertisements: An Analysis of Adolescents’ Momentary and Retrospective Evaluations - Yzer, Marco C. (2011)
Perceived message effectiveness is often used as a diagnostic tool to determine whether a health message is likely to be successful or needs modification before use in an intervention. Yet, published research on the antecedents of perceived effectiveness is scarce and, consequently, little is known about why a message is perceived to be effective or ineffective. The present study’s aim was to identify and test the affective antecedents of perceived effectiveness of antidrug television messages in a sample of 190 adolescents in the 15–19 year age range. Factor-analytical tests of retrospective message evaluation items suggested two dimensions of perceived effectiveness, one that contained items such as convincingness whereas the other contained pleasantness items. Using retrospective data as well as real time valence and arousal ratings, we found that arousal underlies perceived convincingness and valence underlies perceived pleasantness. The results indicated activation of appetitive and defensive motivational systems, which suggests a clear motivational component to the concept of perceived message effectiveness.